Etiology of meningitis from patients suspected of meningitis attending Tribhuvan University Teaching Hospital, Kathmandu, Nepal. - Pandey, Pinkey (2014)
ABSTRACT: Meningitis is an inflammatory infection of the membranes surrounding the brain and spinal cord, which occurs as either a primary disease or secondarily to disease in some other part of the body. Its most frequent causes are Neisseria meningitidis, Streptococcus pneumoniae, and Haemophilus influenzae. The epidemiological trend of acute meningitis varies with time and geography. Information on the relative frequency of the isolation and antibiotic susceptibility patterns of these pathogens is scarce in Nepal. The broad objective of this research was to analyze the various etiological agents of meningitis in all age group patients and to know the antimicrobial susceptibility pattern of bacterial isolates from the cerebrospinal fluids (CSF) of suspected cases of meningitis. In this cross sectional study, a total of 356 CSF specimens were collected from patients suspected of meningitis and processed macroscopically, microscopically and microbiologically by standard microbiological methods in Emergency Lab of TUTH in Kathmandu, Nepal over a period of six months, from March 2014 to August 2014 to determine cytological, biochemical and microbiological parameters. Out of 356 CSF samples, bacterial and fungal culture positivity rate was found to be 16 (4.5%). Among the positive isolates, the most common bacterial isolate was Staphylococcus aureus, 4 (25%). Isolation rate of Cryptococcus neoformans was 3 (18.8%) the only fungal etiology of meningitis which was seen in elderly patients indicating increased susceptibility in immune-compromised status of patients. All bacterial isolates were found to be sensitive against Chloramphenicol. Thus it is concluded that the isolation rate of pathogens from cerebrospinal fluids causing meningitis is low. Chloramphenicol is effective for the treatment of bacterial meningitis. Key words: Meningitis, cytological, biochemical and microbiological parameters, antimicrobial susceptibility.